Correlation of Cytokine Release Syndrome With Prognosis After Chimeric Antigen Receptor T Cell Therapy: Analysis of 54 Patients With Relapsed or Refractory Multiple Myeloma - Wang, Xue; Zhao, Lina; Wang, Jing; Yao, Yue; Wang, Jiaojiao; Ji, Shengwei; Hua, Tian; Wang, Shiyuan; Cheng, Hai; Shi, Ming; Li, Zhenyu; Zeng, Lingyu; et al. (Frontiers in Immunology, 2022)
Although chimeric antigen receptor T (CAR-T) cell therapy has proven to be effective in treating relapsed or refractory multiple myeloma (R/R MM), the severity of cytokine release syndrome (CRS) can affect patient survival and the risk factors for CRS remain an intractable issue. We enrolled 54 patients with R/R MM following combined infusion of anti-CD19 and anti-B-cell maturation antigen (BCMA) CAR-T cells. The results showed the overall response rate was 94% (51/54) after CAR-T cell infusion, with a 100% incidence of CRS, including 47 patients with grade 1-2 (mild) CRS and 7 patients with grade 3-5 (severe) CRS. In the mild CRS group, the median progression-free survival (PFS) was 18.2 months (95% CI, 6.5 to 30.1) and the median overall survival (OS) was not reached yet. In the severe CRS group, median PFS and median OS were 1.9 months (95% CI, 0.2 to 3.8). Further analysis demonstrated that severe CRS had a shorter median PFS and OS than mild CRS (p=0.029, p=0.020). Bone marrow tumor burden was found to be independently associated with CRS. The grade of CRS was positively correlated with six serum cytokines levels including G-CSF, IL-6, IL-8, IP-10, MIP-1a and RANTES. In conclusion, early detection and management of CRS are imperative for the prevention of life-threatening complications and improvement in the survival of patients of CAR-T cell therapy. Clinical Trial Registration www.chictr.org.cn, identifier ChiCTR-OIC-17011272.